Measurement of C-reactive protein in pulmonary tuberculosis patients without treatment and healthy individual - Towhid, Ferdous; Akther, Nazma; Banik, Shyamal Chandra; Rahman, Md Maruf Ur; Akter, Jumruda; Ahmed, Farjana; Ullah, Mohib; Sadique, Sarder Raihan; Mondal, Mosaddek Hossain (Journal of Dhaka National Medical College & Hospital, 2024)
Objective: To assess the C-reactive protein level in pulmonary tuberculosis patients without treatment and healthy individual. Methods: A descriptive, cross sectional study was conducted from January 2016 to June 2016 among 50 pulmonary tuberculosis patients attending at Respiratory Medicine Department of the Dhaka Medical College Hospital and 50 healthy individuals, after obtaining requisite consent from the patients. Data were collected through the interviewing of the patients. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to assess the C-reactive protein level in pulmonary tuberculosis patients and healthy individuals. The study was approved by the institutional ethical committee. Results: In a pool of 50 pulmonary tuberculosis patients without treatment and 50 healthy individuals, Serum CRP level (mg/l) were significantly higher (p <0.001) in PTB than normal individuals. Conclusion: Serum CRP level was significantly higher (p <0.001) in pulmonary tuberculosis patients without treatment. So measurement of CRP level during pulmonary tuberculosis is an important diagnostic and prognostic tools. J. Dhaka National Med. Coll. Hos. 2024; 30 (01): 13-16